Football Traumatology Current Concepts: from Prevention to Treatment - Volpi, Piero.; Volpi, Piero. (Springer Milan : Imprint: Springer, 2006)
Football is probably the most widespread sport in the world: youngsters, adults, women, amateurs, beginners, professionals all make up a legion of practitioners. Lesions associated with football are on the increase and their typology has also changed over the years. Football, like many other sports, has undergone major changes: the increase in the intensity and speed of the game, the modern training methodologies, the technical and tactical innovations are all factors contributing to increased risks of traumatic injury. The footballers, the trainers, the sport's medical staff are asking for greater information and knowledge on the traumatic lesions associated with this sport. The primary role of those who are concerned with the health of footballers is to enforce preventive measures to reduce wherever possible the risks of trauma.